Poverty And Criminality In The Digital Era: An Empirical Study In Indonesia - Pebrianti, Herlina; Agusalim, Lestari; Lestari, Aprima Vista Ajeng (Jurnal Ekonomi STIEP, 2025)
The rapid and widespread development of digital technology has become a major driving force in transforming various aspects of life. This transformation has facilitated human activities across different sectors. However, the fast-paced technological advancements and increasingly accessible information also contribute to the rise of crime. Additionally, poverty can create an unstable environment, which increases the likelihood of individuals being involved in criminal activities. The limitations faced by individuals in poverty make them more susceptible to committing crimes, especially those driven by economic motives. Generally, crime rates tend to increase as the population of the poor rises. This study aims to analyze the impact of poverty on crime in the digital era. The analysis method used is panel data regression with a random effects model, based on panel data from 34 provinces in Indonesia over the period 2010-2022. The results indicate that poverty has a positive and significant effect on crime. However, the internet variable shows a negative and significant effect on crime. Variables such as population density, economic growth, and the Human Development Index (HDI) have a positive and significant effect on crime. Furthermore, variables like the provincial minimum wage and the COVID-19 dummy variable show a negative and significant effect on crime. On the other hand, the open unemployment rate does not have a significant effect on crime. Finally, the interaction between poverty and internet usage has a positive and significant effect on crime.